Occupational Recognition and Immigrant Labor Market Outcomes - Brücker, Herbert; Glitz, Albrecht; Lerche, Adrian; Romiti, Agnese (Journal of Labor Economics, 2021)
We analyze how the formal recognition of foreign qualifications affects immigrants’ labor market outcomes. The empirical analysis is based on a novel German data set that links respondents’ survey information to their administrative records, allowing us to observe immigrants at monthly intervals before, during, and after their application for occupational recognition. We find that 3 years after obtaining recognition, immigrants earn 19.8% higher wages and are 24.5 percentage points more likely to be employed than immigrants in the control group. We further document that occupational recognition leads to full convergence of immigrants’ earnings to those of their native counterparts.